Job recruitment and its relation with job satisfaction from Islamic perspective: An applied study in Jordan / Majed Fawzi Mohammad Abughazalah - Majed Fawzi , Mohammad Abughazalah (2016)
This study strives to investigate the concept of recruitment, its advantages and disadvantages, its procedures and importance. This study also aims to analyze the relation between recruitment and job satisfaction, and its connection with Islamic values and principles in academic environment. Nowadays, many institutions are moving towards creating an integrated system, which covers institutions interaction internally and externally. It includes a new recruitment mechanism which could save time and cost of the institution by considering all possibilities in achieving the recruitment purpose. Thus, data was collected through a questionnaire, which covers all variables - financial reward, academic field, laws and regulations, career environment, and social status. Each hypothesis has a number of questions regarding the variables relationship and its impact on educational institutions (universities), as well as illustrating the importance of job satisfaction from the beginning to the end of contract according to Islamic perspective. The study has been conducted at “Middle East University” and “World Islamic Sciences University” which are applying international characteristics in recruiting the educators from outside Jordan. The data collected was analyzed with the SPSS software, by using T test. The findings reveal that there are relations between recruitment and job satisfaction in all aspects except in financial reward aspect. These findings may contribute to the recruitment system development at universities. These findings also have practical implications for upgrading the quality employment. It also shed light on the importance of experiences exchange among faculties in different countries.